2021
DOI: 10.3390/jpm11040317
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Multi-Session Transcranial Direct Current Stimulation on Social Cognition in Schizophrenia: A Study Protocol for an Open-Label, Single-Arm Trial

Abstract: Backgrounds: Social cognition is defined as the mental operations underlying social behavior. Patients with schizophrenia elicit impairments of social cognition, which is linked to poor real-world functional outcomes. In a previous study, transcranial direct current stimulation (tDCS) improved emotional recognition, a domain of social cognition, in patients with schizophrenia. However, since social cognition was only minimally improved by tDCS when administered on frontal brain areas, investigations on the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…The negative results in previous studies may have been due to the difference in neural circuits governing respective cognitive functions (neurocognition vs. social cognition) (9,20,22). As neural substrates for social cognition include the orbitofrontal cortex, mPFC, STS, and amygdala (20,21), we chose the left STS for anodal stimulation. As expected, tDCS delivered to the skull for this brain area was found to improve ToM (measured by the Hinting Task and the SCSQ), but not neurocognition (measured by the BACS).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The negative results in previous studies may have been due to the difference in neural circuits governing respective cognitive functions (neurocognition vs. social cognition) (9,20,22). As neural substrates for social cognition include the orbitofrontal cortex, mPFC, STS, and amygdala (20,21), we chose the left STS for anodal stimulation. As expected, tDCS delivered to the skull for this brain area was found to improve ToM (measured by the Hinting Task and the SCSQ), but not neurocognition (measured by the BACS).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, only one study reported facilitative effects of tDCS on emotion recognition with the Fp1 as the anodal site (19). Unlike the case for neurocognition, the neural network for social cognition may include the orbitofrontal cortex, medial prefrontal cortex (mPFC), superior temporal sulcus (STS), and amygdala; functional connectivity of these brain regions is attenuated in schizophrenia (20)(21)(22). Accordingly, impaired connectivity between these brain regions is associated with poor social cognitive functioning (6,9).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This initiative to develop a comprehensive set of social cognition tests is embodied by the Evaluation Study of Social Cognition Measures in Japan (ESCoM), as reported by Kubota et al [9]. As a novel treatment approach, Yamada et al [10] are conducting a clinical trial to determine if transcranial direct current stimulation on the temporal lobe sulcus regions alleviates social cognition impairment in schizophrenia.…”
mentioning
confidence: 99%